A Practical Approach to Diagnosing Peripheral Neuropathies - Jacoby, Nuri; Anziska, Yaacov (Seminars in Neurology, 2024)
Polyneuropathies are common, with the incidence increasing with older age. The causes of polyneuropathies are diverse and numerous, and it can be challenging for clinicians to determine the etiology of a particular patient's neuropathy. In this article, we systematically detail a practical approach to polyneuropathies, beginning with the most important aspects of the workup, the history and physical. We then discuss the limited diagnostic approach required for patients who present with a distal symmetric polyneuropathy and the more comprehensive approach for patients who present with other neuropathy subtypes.
Keywords: Peripheral neuropathy; Polyneuropathy; Electrodiagnostic studies